Design, Advertising, And Product Quality: Its Influence on The Decision to Buy Halal Cosmetic - Sugeng Nugroho Hadi; Salihah Khairawati; Ihda Nur Fatihah; Ismail Yusanto Yusanto; Muhajirin Muhajirin (International Journal of Economics, Social Science, Entrepreneurship and Technology (IJESET), 2022)
This study aims to analyze the effect of the design, advertising, and quality of halal cosmetic products under the Safi brand on the buying decisions of Muslim consumers. To fulfill the research objectives above, the research was conducted using quantitative methods, with incidental sampling, and using multiple linear regression including correlation test, determination test, multiple linear regression test, t-test, and F test with IBM SPSS version 23 program. Based on the results of the analysis, it can be concluded that: design has no significant effect on Consumer Buying Decisions, Advertising has a positive and significant influence on Consumer Buying Decisions, and quality does not significantly affect Consumer Buying Decisions. Meanwhile, in joint testing, all variables have a real and significant effect on Safi's Consumer Buying Decision. The management should maintain its marketing program with attractive advertisements to continue to compete with other competitors.